A π‐Conjugated, Covalent Phosphinine Framework. Issue 53 (13th August 2019) - Huang, Jieyang; Tarábek, Ján; Kulkarni, Ranjit; Wang, Cui; Dračínský, Martin; Smales, Glen J.; Tian, Yu; Ren, Shijie; Pauw, Brian R.; Resch‐Genger, Ute; Bojdys, Michael J.
Abstract: Structural modularity of polymer frameworks is a key advantage of covalent organic polymers, however, only C, N, O, Si, and S have found their way into their building blocks so far. Here, the toolbox available to polymer and materials chemists is expanded by one additional nonmetal, phosphorus. Starting with a building block that contains a λ 5 ‐phosphinine (C5 P) moiety, a number of polymerization protocols are evaluated, finally obtaining a π‐conjugated, covalent phosphinine‐based framework (CPF‐1) through Suzuki–Miyaura coupling. CPF‐1 is a weakly porous polymer glass (72.4 m 2  g −1 BET at 77 K) with green fluorescence ( λ max =546 nm) and extremely high thermal stability. The polymer catalyzes hydrogen evolution from water under UV and visible light irradiation without the need for additional co‐catalyst at a rate of 33.3 μmol h −1  g −1 . These results demonstrate for the first time the incorporation of the phosphinine motif into a complex polymer framework. Phosphinine‐based frameworks show promising electronic and optical properties, which might spark future interest in their applications in light‐emitting devices and heterogeneous catalysis. Abstract : Phosphinine in π : For the first time since its synthesis in 1966, the six‐membered phosphinine ring is incorporated into a π‐conjugated polymer. The phosphinine‐based framework (CPF‐1) has a high concentration of paramagnetic species, high thermal stability, green fluorescence, and shows activity in photocatalytic water splitting.